2022
DOI: 10.33578/jtlee.v5i2.7938
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Project Based Learning Model toward Students’ Creative Thinking Skill on Civics Subject

Abstract: This study aimed to determine the effects of the Project Based Learning model on students' creative thinking skills in Civics subject on Concepts, Values, Morals and Norms topic. This is a quantitative research, using a quasi-experimental method with a non-equivalent control group design. Subjects of this research were 74 second year students in class A and B of Elementary School Teacher Education Program, Nusa Cendana University. Results were analyzed and tested for its t value through independent sample t te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…In other words, the PjBL model is suitable for application both among students with a Field-Independent (FI) cognitive style and those with a Field-Dependent (FD) cognitive style. These research findings are supported by previous studies (Koroh et al, 2022;Lou et al, 2017;Usmeldi, 2019;Yustina et al, 2020) that found the PjBL model can enhance students' creativity. In this current study, the creativity of both cognitive style groups (FD/FI) experienced improvement (based on average pre-test-post-test parameters).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In other words, the PjBL model is suitable for application both among students with a Field-Independent (FI) cognitive style and those with a Field-Dependent (FD) cognitive style. These research findings are supported by previous studies (Koroh et al, 2022;Lou et al, 2017;Usmeldi, 2019;Yustina et al, 2020) that found the PjBL model can enhance students' creativity. In this current study, the creativity of both cognitive style groups (FD/FI) experienced improvement (based on average pre-test-post-test parameters).…”
Section: Discussionsupporting
confidence: 88%
“…Empirical studies on the implementation of the Project-Based Learning (PjBL) model in enhancing creativity have been conducted in several previous studies (Koroh, Lehan, Treesly, & Koro, 2022;Lou, Chou, Shih, & Chung, 2017;Yustina, Syafii, & Vebrianto, 2020). The results show that the PjBL model can improve students' creativity at a moderate level, with varying N-gain scores.…”
Section: Introductionmentioning
confidence: 99%
“…CT is very important especially for educators to develop learning because creativity is the basis for human development and survival (Kaplan, 2019). Project-based learning encourages the teaching and learning process, involves students in the learning process, motivates, and increases student creativity (Astuti et al, 2022;Cahyani, 2021;Koroh et al, 2022;Mursid, 2022). Therefore, project-based learning is the right learning model to increase creativity because it requires students to be directly involved in their learning.…”
Section: The Effect Of Pjbfl Media On Ctmentioning
confidence: 99%